2009
DOI: 10.25011/cim.v32i4.6618
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin has different mechanisms in type 1 and type 2 diabetes with C-peptide link

Abstract: Clin Invest Med 2009; 32 (4): E271-E279. AbstractPurpose: Adiponectin (ApN) is considered to be responsible for reduction of inflammation and is known to be included in lipid metabolism. This study was designed to assess the role of adiponectin in patients with type 1 and type 2 diabetes and to determine parameters important in the prediction of adiponectin. Methods: Adiponectin, high sensitive C-reactive protein, fibrinogen, homocysteine, C-peptide, and lipid panel in addition to clinical and laboratory param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
4
10
0
Order By: Relevance
“…The study observed no significant (p>0.05) differences in the serum adiponectin levels of the diabetics and the non-diabetics population studied. Similar observation has been reported by a previous study 12 between type 2 diabetics and controls. Type 2 diabetic subjects recruited in this study have been on sulphonyurea treatment from the time of diagnosis to time analysis was carried out.…”
Section: Discussionsupporting
confidence: 92%
“…The study observed no significant (p>0.05) differences in the serum adiponectin levels of the diabetics and the non-diabetics population studied. Similar observation has been reported by a previous study 12 between type 2 diabetics and controls. Type 2 diabetic subjects recruited in this study have been on sulphonyurea treatment from the time of diagnosis to time analysis was carried out.…”
Section: Discussionsupporting
confidence: 92%
“…But our results are contrary to Lindström et al (49) who reported a non-significant correlation of adiponectin with TAG but a direct association with TC. In our results, ACR was not correlated to adiponectin, which is supported by the results of Ljubic et al (50). …”
Section: Discussionsupporting
confidence: 91%
“…[25]. Another study of Ljubic et al also reported the similar result [26]. Furthermore, a crosssectional study of Streja et al elucidated no association of hs-CRP with the complications of diabetes [27].…”
Section: Discussionmentioning
confidence: 72%